2022
DOI: 10.1111/ane.13622
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and predictors of non‐thrombolysis in patients with acute ischemic stroke admitted within 4.5 h

Abstract: Objectives Thrombolytic treatment in acute ischemic stroke (AIS) reduces stroke‐related disability. Nearly 40% of all patients with AIS (<4.5 h) receive thrombolysis, but there is a large variation in the use between hospitals. Little is known about reasons and predictors for not giving thrombolytic treatment. Therefore, we aimed to investigate reasons for non‐thrombolysis in patients admitted within 4.5 h. Methods All patients with AIS (<4.5 h) admitted to Akershus University Hospital, Norway, between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The most cited reasons for not administering IVT were minor and improving symptoms. Other studies inside and outside of the United States have shown similar results 5,6 …”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The most cited reasons for not administering IVT were minor and improving symptoms. Other studies inside and outside of the United States have shown similar results 5,6 …”
Section: Introductionsupporting
confidence: 62%
“…Other studies inside and outside of the United States have shown similar results. 5,6 LVOS patients typically present with more severe deficits, which should make them easier to identify. For patients with LVOS, endovascular treatment, which shows better results than medical management alone, is the mainstay of treatment.…”
Section: Importancementioning
confidence: 99%
“…In this issue of Acta Neurologica Scandinavica , Bergh et al present a study in which they account for reasons why thrombolysis is not given to patients with ischemic stroke 1 . They wisely conclude that increasing the use of thrombolysis within the time window of 4.5 h must be weighed against possible harms.…”
mentioning
confidence: 99%